2017
DOI: 10.1080/13561820.2016.1261098
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between team climate and interprofessional collaboration: Preliminary results of a mixed methods study

Abstract: Relational and organisational factors are key elements of interprofessional collaboration (IPC) and team climate. Few studies have explored the relationship between IPC and team climate. This article presents a study that aimed to explore IPC in primary healthcare teams and understand how the assessment of team climate may provide insights into IPC. A mixed methods study design was adopted. In Stage 1 of the study, team climate was assessed using the Team Climate Inventory with 159 professionals in 18 interpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 8 publications
3
24
0
7
Order By: Relevance
“…For example, Weiss, Hoegl, and Gibbert (2011), drawing on research on financial resource scarcity (Hoegl, Gibbert, & Mazursky, 2008) and the 'path of least resistance' work by Ward (1994), found that team innovation climate predicted higher levels of product quality and project efficiency, but only in projects where there were financial resource constraints. Agreli, Peduzzi, and Bailey (2017) found that in teams in which team climate was stronger, they reported higher levels of communication and mutual support. Agreli, Peduzzi, and Bailey (2017) found that in teams in which team climate was stronger, they reported higher levels of communication and mutual support.…”
Section: Team Level Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Weiss, Hoegl, and Gibbert (2011), drawing on research on financial resource scarcity (Hoegl, Gibbert, & Mazursky, 2008) and the 'path of least resistance' work by Ward (1994), found that team innovation climate predicted higher levels of product quality and project efficiency, but only in projects where there were financial resource constraints. Agreli, Peduzzi, and Bailey (2017) found that in teams in which team climate was stronger, they reported higher levels of communication and mutual support. Agreli, Peduzzi, and Bailey (2017) found that in teams in which team climate was stronger, they reported higher levels of communication and mutual support.…”
Section: Team Level Outcomesmentioning
confidence: 97%
“…Pei (2017) found a strong relationship between team innovation climate and team creativity. Agreli, Peduzzi, and Bailey (2017) found that in teams in which team climate was stronger, they reported higher levels of communication and mutual support. Although, Bower et al (2003) and Cramm, Strating, and Nieboer (2014) found a strong link between team innovation climate and quality of care provided to patients in general medical practices and chronic care, respectively, Goh et al (2009) found no link between team innovation climate and quality of care provided to patients in general practice.…”
Section: Team Level Outcomesmentioning
confidence: 97%
“…In addition, it is essential to achieve managerial goals, as it affects work process and motivation of workers. However, in order to achieve the goals, it is necessary to promote satisfaction and pleasure in the work environment, minimize hierarchical rigidity, and implement participatory management (2) . Team climate also refers to the design of teamwork as it involves the integration and collaboration among members of the same team (3) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to consolidate teamwork in the field of Health, it is necessary to establish objectives, to have concrete goals well defined and common to the group of workers. Thus, based on individual and group growth, it is possible to contribute to the development of care that is centered on the user and his community (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation